THE EFFECTS OF CALSİUM ION ON ISOMETRIC CONTRACTION PROPERTIES OF AND FATIQUA IN ISLOLATED FROG SKELETAL MUSCLES. - Özmerdivenli, Recep; Süer, Cem (Gazi Üniversitesi, 2000)
Although it has been known that the role of extracellular Cst' on the contraction of the skeletal muscle is negligible, recent investigations found out contrary data. Owing to these current facts, the goal of this study is to search for the impact of the extracellular calcium ions on the periodical twithc parameters of the isolated frog muscles. In our research we used isolated skeletal muscle preparations obtained from both sexes of Rana Ridibunda frogs weighing 60-70 g. The isometric muscle twitchs, produced by electrical stimulus models are recorded using polygraph and calculation of twithc parameters (CT, RT, 1/2 RT, TT) was performed.There was statistical differences between the pre and post fatique twitch properties of gastrrecnemius and extensor digitorum longus muscles. It was found that in both muscle groups the twitch period in the recording solution containing calcium was longer than calcium-free. While gastrecnemius muscle developped fatigue by stimuli between 1-5 Hz. under both media with or without calcium, extensor digitorum longus muscle did not developped fatique when calcium containing recording solution was used. It was also discovered that the isometric twich properties of the extensor digitorum and gastrecnemius muscles towards 1-5 Hz electrical stimuli models do not vary according to media with/without calcium. In our study the difference of twitch parameters between two muscle groups may be depent upon their metabolism as well as differences in their fast and slow twitch fibre proportion and content. In conclusion, the results of this study indicates that extracellular calcium ions regulates calcium release from sarcoplasmic reticulum in a calcium-induced calcium release mechanism dependent manner.

İskelet kaslarının kasılmasında ekstraselüler kalsiyumun rolünün önemli olmadığı görüşü, son yıllarda yapılan çalışmalarda aksi bulgular elde edilmesi ile değişikliğe uğramıştır. Bu bulguların ışığı altında bu çalışmada; ekstrasellüler Caf"un iskelet kası kasılmasındaki rolü ve bu amaçla izole kurbağa kasında zamansa! sarsı parametrelerine ekstrasellüler kalsiyum iyonunun etkisinin araştırılması planlandı. Araştırmamızda ağırlıkları 60-75 gr arasında değişen her iki cinsten Rana Ridibunda türü kurbağalardan elde edilen izole iskelet kas preparatları kullanıldı. Elektriksel uyarım modelleri ile oluşturulan izometrik kas sarsılan poligrafik sistem ile kaydedildi ve zamansal sarsı parametreleri (CT, RT, 1/2 RT, TT) hesaplandı.    Yorgunluk öncesi zamansal sarsı parametreleri gastroknemius ve ekstensor digitorum longus kaslarında farklılık gösterdi. Her iki kas grubunun da kalsiyumlu ekstraselüler solüsyon mevcudiyetinde kalsiyumsuz solüsyon kullanımına göre daha uzun sarsı sürelerine sahip olduğu bulundu. Gastroknemius kası hem kalsiyumlu hem de kalsiyumsuz ortamda 1-5 Hz arasındaki uyarımlarla yorulabilirken, ekstonsor digitorum longus kası kalsiyumlu ortamda yorulmadı. Gastroknemius kasının kalsiyumlu ve kalsiyumsuz ortamlarda 1-5 Hz arasında özellikle gevşeme parametreleri diğer kastan istatistiksel olarak anlamalı düzeyde uzun bulundu (p<0.05).    Çalışmamızda sarsı parametrelerinin iki kas grubu arasında farklılık göstermesi, iki kas grubunun metabolizmalarının farklılığı, hızlı/yavaş lif oranlarının birbirinden farklı olması ile izah edilebilir. Bu çalışmada; ekstrasellüler kalsiyum iyonlarının kalsiyum tetiklemeli kalsiyum salıverilmesi mekanizması ile sarkoplazmik retikulumdan kalsiyum salıverilmesinin regülasyonunda rolü olduğu sonucuna varıldı.
IZOLE KURBAĞA KASLARıNDA KALSIYUM IYONUNUN IZOMETRÎK SARSı KARAKTERLERI VE YORGUNLUK OLUŞUMA ETKISI
Keywords: Sports Medicine; Spor Hekimliği